IMPLEMENTATION OF THE RESTORATIVE JUSTICE CONCEPT BASED ON POLICE REGULATION NO. 8 OF 2021 IN CRIMINAL OFFENSES - Bahri, M Samsul; Patrianto, Dr Bangun (jfpublisher, 2025)
Bankruptcy occurs when a debtor is unable to fulfill debt obligations to creditors, often due to financial mismanagement or market miscalculations that lead to business failure. In bankruptcy proceedings, public seizure aims to protect the debtor's assets to prevent their transfer or misuse. Conversely, asset seizure in criminal cases serves as a means to secure evidence or proceeds of crime, ensuring such assets remain intact for the investigation and trial process. These dual legal interests can create procedural conflicts, particularly when the same asset is subject to both bankruptcy proceedings and criminal seizure. This research examines the normative contradictions between Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations and the Indonesian Criminal Procedure Code regarding the priority of seizures. Article 31(2) of the Bankruptcy Law declares that all previous seizures are null and void upon bankruptcy declaration, while Article 39(2) of the Criminal Procedure Code permits the seizure of property even if it is involved in civil or bankruptcy proceedings. This legal overlap raises critical questions about asset management and legal certainty when bankruptcy and criminal processes intersect. The study aims to analyze this conflict and propose a solution to balance the rights of creditors with the needs of criminal law enforcement.